Respuesta :

x+y=-1
x-3y=11
------------- (subtract equation)
4y = -12
y = -12/4
y= -3
-------------- (substitute y)

x-3=-1
x=-1+3
x=2


Answer ----> A (2,-3)





-5x-3y=12
x-3y=-6

you want to multiply the top equation by -1 to swap the signs and make the x's positive like the bottom equation

5x+3y=-12
x-3y=-6

then you have to multiply every value in the bottom equation by 5 so you are able to subtract it from the top equation

5x+3y=-12
5x-15y=-30
---------------- (subtract)
18y=18
y=18/18
y=1
------------------ (substitute y)
x-3=-6
x=-6+3
x=-3

answer = (-3,1)